Ways of living: Tim Ingold on culture, biology and the anthropological task - Luis Fernando Angosto Ferrández (Antropólogos Iberoamericanos en Red, 2013)
Life is a university. Tim Ingold reminds us of something that we have often heard in bohemian circles. Life is fieldwork and fieldwork is life. Those who are familiar with Ingold’s oeuvre will not be surprised by this statement; for those who are not, here is an extraordinary opportunity to step into it. In this conversation, Ingold makes an overview of some of his central ideas about what makes us human, but he is also invited to critically reflect on questions of anthropological method and theory, as well as on the role of our discipline in the big contemporary debates. Along with Ingold, we welcome here an anthropology that thinks of (and not only shows) diverse ways of living.